Study of Vibration Characteristics of Cantilever Beams of Different Materials - Arora, Sanpreet Singh (My University, 2012)
ABSTRACT Estimating damping in structure made of different materials (steel, brass, aluminum) and processes still remains as one of the biggest challengers. All materials posses certain amount of internal damping, which manifested as dissipation of energy from the system. This energy in a vibratory system is either dissipated into heat or radiated away from the system. Material damping or internal damping contributes to about 10-15% of total system damping. The main objective of this thesis is to estimate the damping ratio, natural frequency of aluminum, brass and steel by free vibration analysis experimentally & verify theoretically. Cantilever beams of required size & shape are prepared for experimental purpose & damping ratio is investigated. Damping ratio is determined by half-power bandwidth method. It is observed that damping ratio is higher for steel than brass than aluminum. This thesis presents results of an experimental free vibration analysis of beams made with different materials such as Brass, aluminum and steel. The theoretical modal analysis was also done in ANSYS to compare the results. The beams were excited using wooden mallet and signals were catched with the help of accelerometer attached with VIB SCANNER instruments. Then FRF (Frequency response functions) were obtained using omnitrend software to identify fundamental natural frequency and damping ratios.
M.E. (CAD/CAM and Robotics)
Keywords: Vibration Characteristics; Cantilever Beams